Pengaruh Komunikasi Politik Melalui Media Sosial Instagram Terhadap Tingkat Partisipasi Politik Mahasiswa Prodi PPKN Universitas Jambi Pada Pilpres Tahun 2019 - Cahya, Dyah Estyani; Anderson, Irzal; Sariani, Dona (Civic Education Perspective Journal, 2021)
Abstract: This research is motivated by the massive use of social media, especially Instagram among students of the Jambi University Civics Study Program, moreover, Instagram social media is used as a source of political information, especially during the 2019 Presidential Election. The purpose of this research is to test whether there is an influence between communication Political participation through social media Instagram on the level of political participation of students from the Civics Education Study Program at the University of Jambi in the 2019 Presidential Election. This research is an Ex Post Facto study with a quantitative approach which is generally carried out in the Pancasila and Citizenship Education study program at the University of Jambi. The data collection technique used is a questionnaire (questionnaire). Based on the results of data analysis that has been carried out using a simple linear regression model with the help of the SPSS version 24 application, it is evident that the variable of political communication through social media Instagram (X) has a significant influence on political participation (Y). The magnitude of the influence between variables in the analysis of political communication through Instagram social media on political participation can be seen from the coefficient of determination RÂ² which is 0.409 meaning that the effective contribution given by political communication through Instagram social media to political participation is 40.9% while the remaining 59.1% is a contribution from other variables outside of the variables studied by researchers.